2010
DOI: 10.1242/jeb.045278
|View full text |Cite
|
Sign up to set email alerts
|

Arboreal locomotion in rats – the challenge of maintaining stability

Abstract: SUMMARY Arboreal locomotion has mainly been looked at to date in the context of investigations into the specialization of primates and other ‘arboreally adapted’ animals. The feat of moving on branches as small or smaller than the body's diameter was tested in rats (Rattus norvegicus) as they moved on horizontal poles of different diameters. The data were compared with data pertaining to terrestrial locomotion. We investigated three-dimensional kinematics and dynamics using biplanar cineradiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
113
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 36 publications
14
113
2
Order By: Relevance
“…In addition, tetrapods moving on small branches reduce the distance of the body to the substrate to minimize the vertical oscillation of the CoM that causes rolling moments (e.g. Schmitt and Lemelin, 2002;Higham and Jayne, 2004a;Schmidt and Fischer, 2010). Other adjustments include the reduction of speed, stride frequency and peak forces (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, tetrapods moving on small branches reduce the distance of the body to the substrate to minimize the vertical oscillation of the CoM that causes rolling moments (e.g. Schmitt and Lemelin, 2002;Higham and Jayne, 2004a;Schmidt and Fischer, 2010). Other adjustments include the reduction of speed, stride frequency and peak forces (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of substrate orientation on small-branch locomotion are not as well known, as studies of horizontal branch locomotion (e.g. Schmitt, 2010) and almost all studies focusing on climbing to date do not include kinetics (mammals: Nakano, 2002;Nyakatura et al, 2008;Schmidt and Fischer, 2010;Shapiro and Young, 2010;Stevens et al, 2011;lizards: Higham and Jayne, 2004a;Higham and Jayne, 2004b;Foster and Higham, 2012). Besides the studies of vertical climbing in Old and New World monkeys (Hirasaki et al, 1993;Hirasaki et al, 2000;Nakano, 2002;Hanna and Schmitt, 2011), only one study to date has investigated the kinetics of small-branch locomotion on shallow inclines and declines [in Monodelphis domestica (Lammers, 2007)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice and rats are competent climbers and possess good grasping skills (Schmidt and Fischer 2010) that are thought to be guided by a combination of olfactory, visual and tactile cues (Bhattacharyya and Bhalla 2015;Niederschuh et al 2015;Schroeder and Ritt 2016). However, the tactile whisker sense plays a primary role in environmental exploration and locomotion in both rats and mice (Vincent 1912;Watson 1907).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined locomotor ontogeny in an environment where the 481 Locomotor ontogeny in sugar gliders natural diversity of substrates is represented. Field and especially lab-based studies of arboreal mammals have identified detailed kinematic or kinetic locomotor adjustments to substrate variation in adults (McClearn, 1992;Vilensky et al, 1994;Lemelin et al, 2003;Schmitt, 2003a;Schmitt and Hanna, 2004;Delciellos and Vieira, 2006;Stevens, 2006;Scheibe et al, 2007;Stevens, 2007;Nyakatura et al, 2008;Carlson and Demes, 2010;Nyakatura and Heymann, 2010;Schmidt and Fischer, 2010) but much less extensively from an ontogenetic perspective (but see Young, 2009a;Young, 2009b). In contrast, naturalistic studies of locomotor ontogeny in arboreal taxa (mainly primates) have mostly focused on ontogenetic shifts in locomotor and substrate preferences (e.g.…”
Section: Introductionmentioning
confidence: 99%